Organizational Citizenship Behavior and Religiosity: A Literature Review on Psychological Dynamics in Organizations - Ahmad Alyani Addarain; Gumgum Gumelar Fajar Rakhman; Yufiarti Yufiarti; Zarina Akbar (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2025)
This study explores the relationship between religiosity and Organizational Citizenship Behavior (OCB) within contemporary organizations by adopting a positive psychology perspective. OCB is defined as discretionary behaviors by employees that go beyond their formal job duties and contribute positively to the overall functioning and success of the organization. Examples include helping colleagues, being punctual, and demonstrating initiative, which foster a cooperative and productive work environment. Religiosity, on the other hand, is understood as a belief system that shapes an individual’s values, attitudes, and behaviors, both intrinsically—stemming from internal spiritual commitment—and extrinsically—motivated by external social or cultural influences. Through a systematic review of ten national and international academic journals, this study identifies several common dimensions of OCB, such as altruism (helping others selflessly), civic virtue (active and responsible participation in organizational affairs), and conscientiousness (going beyond minimal job requirements). The findings reveal a consistent positive correlation between religiosity and OCB, especially in sectors like education, Islamic banking, and healthcare, where religious principles strongly influence organizational culture. The integration of religious values into organizational practices encourages employees to exhibit behaviors that promote harmony, ethical conduct, and a sense of community within the workplace. This is particularly evident in employees who possess high levels of intrinsic religiosity, as their internalized beliefs motivate them to engage in prosocial actions that benefit the organization. The study recommends that human resource management strategies incorporate religious or spiritual values to cultivate a positive organizational culture. Such integration can be achieved through training programs, leadership development, and reward systems that emphasize ethical behavior and social responsibility, ultimately leading to improved employee satisfaction, loyalty, and overall organizational performance.